AN ANALYSIS ON THE IMPACT OF A BROKEN FAMILY TOWARDS THE CHILDREN’S BEHAVIOUR AS SEEN IN NOVEL RAINBIRDS - Novi Diana; Ahmad Muhid; Didit Kurniadi (Universitas Aki, 2021)
In this article, the topic is about the impact from a broken family towards the children behaviour base on the novel RAINBIRDS. The goal of this research is to analyze it under the title “An Analysis on The Impact of A Broken Family Towards The Children’s Behaviour as Seen in Novel: Rainbirds”. In the analysis, there are two methods of research; firstly, library research then taking opinion from experts to support the idea. To get the data, structural approach is used because the discussion is about the structure of story such as character and characterization. It uses the theory of B.F Skinner about behaviorism and Sigmund Freud about Id, Ego and Superego to analyze deeply about the behaviour of the characters and find out about their personality that leads to their actions. From the discussion, based on the psychology theory mentioned, Ren Ishida is mostly superego type of person because he often does something good although he was id-driven caused from his childhood experience in his family. Rio Nakajima on the other hand, is mostly id-driven, she tends to do action as she please without realizing the impact of her action towards herself. Each character has their struggle. Each character is battling with their problem and reacts in a different ways. This story is very interesting because through the story we can learn more about the struggle children will endure if they have a broken family and how that problem impacts their life.